Environmental Conservation of Coral Reefs in the Wakatobi Region Based on Islamic Education and Customary Law Approaches - Karim, Nurdin; Hadisi, La; Ramli, Ramli; Lubis, Maesaroh; Anhusadar, Laode (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Currently, coral reef conservation in the Wakatobi area is facing various environmental problems that threaten the coral reef ecosystem. These environmental problems are closely related to various community activities, both local, domestic and international. Based on this problem, this research aims to educate the public about how to preserve the coral reefs of Wakatobi, Southeast Sulawesi. This research uses the Participatory Action Research (PTR) method using an Islamic education and customary law approach. The results of this research provide an illustration that preserving the Wakatobi coral reef environment requires a comprehensive approach and from various perspectives. Islamic education instills moral and ethical awareness in protecting the Wakatobi coral reef environment. Customary law provides a stronger protection mechanism for coral reefs. The synergy between the two strengthens conservation efforts by building awareness and behavior based on religious and cultural values. Thus, through Islamic education that conveys formal and informal religious messages supported by traditional values carried out by ulama or preachers, community character can support environmental sustainability. So, coral reefs as part of the marine ecosystem are very important so that the survival of fish and various other habitats can be well maintained.